Analisis efektivitas ship management untuk optimalisasi kinerja di era industry 5.0 - Mudjiono, Gadha Septio; Susanti, Susanti; Anggraini, Shinta Dwi Nur; Rozaq, Khoirur (Universitas Negeri Surabaya, 2024)
In supporting the success of a project in a company, management issues often become an important factor in implementation in the field. Likewise, PT PAL Marine Service (PT PALMARS) operates in Surabaya, East Java. This company operates in the service sector and offers several services to support the company's progress, one of which is ship management. Therefore, to analyze the effectiveness of ship management in optimizing organizational performance in the Industrial Era 5.0, a case study was carried out at PT. PAL Marine Service (PT PALMARS) in Surabaya City, East Java. In this analysis, we will focus on four important perspectives that can influence the effectiveness of ship management through the balanced scorecard method. The independent variables consist of a customer perspective, an internal business process perspective, and a learning and growth perspective. The dependent variable is performance optimization. The sample or key research informants are the majority of lines involved in ship management activities: the Secretary, Marketing Department, Department of Accounting and Tax, Department of Finance and HR, M2KL Department, Operations, Engineering, and Procurement Departments, and the ship's crew. Data collection techniques used to measure organizational effectiveness are case study techniques, surveys/observations, data analysis, literature reviews, documentation, and interviews. The data analysis stages are data collection, reduction, display, and conclusion.